1972
DOI: 10.1079/bjn19720108
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of rumen ciliate protozoa in cattle given restricted amounts of a barley diet

Abstract: I . Two pairs of Friesian steers were changed from ad lib. to restricted intake of a pelleted barley diet and were maintained on this latter intake for periods of 18 or 25 weeks. The restricted level of intake was 70 g/kg0-73 and was adjusted weekly according to individual live weights. The daily allowance was given in three equal feeds during day-time.2. After an initial period of 9 weeks on the restricted diet, during which all four animals were kept free of rumen ciliate protozoa, one member of each pair wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 20 publications
3
22
1
1
Order By: Relevance
“…It is generally accepted that highly acidic pH values in the rumen can inhibit the growth of ciliates (Purser and Moir, 1959) and may even cause their complete elimination (Eadie et al, 1970;Whitelaw et al, 1972;Rung et al, 1986). The decline in the number of entodiniomorphid ciliates noted here during the 3 h following the meal in the rumen juice was always observed in the numerous experiments we carried out.…”
Section: Discussionsupporting
confidence: 52%
“…It is generally accepted that highly acidic pH values in the rumen can inhibit the growth of ciliates (Purser and Moir, 1959) and may even cause their complete elimination (Eadie et al, 1970;Whitelaw et al, 1972;Rung et al, 1986). The decline in the number of entodiniomorphid ciliates noted here during the 3 h following the meal in the rumen juice was always observed in the numerous experiments we carried out.…”
Section: Discussionsupporting
confidence: 52%
“…These factors may have acted most unfavorably on the bacterial number in the rumen on the 1:1 barley-to-hay diet in this experiment. Some researchers have reported that the viable percentage of total count was greater for highconcentrate than for high-roughage diets (1,4,5,16), and that this viable rate was lower with a restricted concentrate diet (17). Similarly, in this experiment, the viable rate dropped to below 10% when hay proportion exceeded one half.…”
Section: Discussionmentioning
confidence: 52%
“…This showed that these chained cocci are similar to Peptostreptococcus rather than Megasphaera elsdenii. This kind of bacterium was reported by WHiTELAW et al (17) and THOMSON et al (19) as a gram-variable chained coccus. They were observed in the gram film prepared from the rumen contents of animals fed restricted amounts of barley or a high proportion of concentrate and those in which the rumen pH was kept at relatively high levels.…”
Section: Discussionmentioning
confidence: 91%
“…WHITELAW et al 26) reported an increased plasma glucose in ciliate-free steers and suggested it to be directly related to the higher concentration of rumen propionic acid in these animals.…”
Section: Discussionmentioning
confidence: 99%